1991
DOI: 10.1071/ar9910325
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of grain quality results from wheat variety trials with reference to high temperature stress

Abstract: Grain quality results for variety trials extending over 27 years (3 sites and 5 varieties) were compared with the temperature profiles during the grain filling period (56 days prior to harvest) to determine the effects on quality of high temperatures (>35�C) during this period of growth. Heat stress episodes have been frequent at two (Narrabri, N.S.W., and Turretfield, S.A.) of the three sites studied; spring temperatures were more moderate at the third site, Wongan Hills, W.A. There were highly significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 6 publications
1
26
1
3
Order By: Relevance
“…Depreendese desse fato que, no estádio inicial de enchimento de grãos, as plantas sejam mais sensíveis ao estresse pelo calor que em estádios mais avançados, nos quais, conforme descrito anteriormente, a temperatura elevada correlacionou-se positivamente com o peso de mil grãos e com o rendimento de grãos. Ao contrário dos resultados obtidos nesse trabalho, dados de literatura indicaram que a influência de elevada temperatura (acima de 30ºC) afetou negativamente a força de glúten [8,9,26,30].…”
Section: -Resultados E Discussãounclassified
“…Depreendese desse fato que, no estádio inicial de enchimento de grãos, as plantas sejam mais sensíveis ao estresse pelo calor que em estádios mais avançados, nos quais, conforme descrito anteriormente, a temperatura elevada correlacionou-se positivamente com o peso de mil grãos e com o rendimento de grãos. Ao contrário dos resultados obtidos nesse trabalho, dados de literatura indicaram que a influência de elevada temperatura (acima de 30ºC) afetou negativamente a força de glúten [8,9,26,30].…”
Section: -Resultados E Discussãounclassified
“…Other factors such as leaf senescence (A1- Khatib & Paulsen, 1984;Kuroyanagi & Paulsen, 1985) and adverse physiological and biochemical changes (Berry & Bjorkman, 1980;A1-Khatib & Paulsen, 1984;Blum, 1986;Jenner, 1991aJenner, , 1991b) also contribute to low production under high temperatures. Recent studies (Blumenthal et al, 1991a(Blumenthal et al, , 1991bRandall & Moss, 1990) indicated that high temperature during the grain-filling stage had adverse effects on breadmaking quality.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of heat stress after anthesis can integrate plant responses to periods with moderate high temperatures (25/32ºC) (Chinoy, 1947;Wardlaw et al, 1989) and plant behaviors to short periods with high temperatures (higher than 32ºC) (Randall and Moss, 1990;Blumenthal et al, 1991). In a previous study, our research group, working on heat stress after anthesis (Maçãs et al, 2000;Dias et al, 2008, found that Triticum aestivum L. genotype Sever is more tolerant than the genotype Golia and that Triticum turgidum subsp.…”
Section: Resultsmentioning
confidence: 99%